Self-regulated learning and intrinsic motivation in students of the UNMSM - Torres Garagundo, Vanessa (2021)
This research includes a scientific contribution that allowed determining the relationship between self-regulated learning and intrinsic motivation in students of the IV cycle of the Professional School of Physical Education of the Faculty of Education of the Universidad Nacional Mayor de San Marcos. It was developed a quantitative approach, with the bases of the correlational-descriptive and non-experimental design. The surveys were applied to 91 students and allowed establishing a relationship between the variables. Thus, it was concluded that there is an association and a direct and highly significant relationship between self-regulated learning and intrinsic motivation of the study population.